Exponential stability and synchronization results for Caputo fractional order impulsive differential equation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper studies exponential stability results for Caputo fractional order impulsive differential equations. We derive some new sufficient conditions for the given system using Convex Lyapunov function and matrix inequality approach. In addition we have incorporated the discussion of exponential synchronization for the error system derived from the given drive system and its response system. The obtained results are validated through fractional order Lorenz system